2020
DOI: 10.2147/cmar.s262279
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA LINC00173 Promotes NUTF2 Expression Through Sponging miR-765 and Facilitates Tumorigenesis in Glioma</p>

et al.

Abstract: Background: Glioma is one of the leading causes of cancer-related deaths. This study aimed to investigate the function and mechanism of long noncoding RNA (lncRNA) LINC00173 in the regulation of glioma progression. Methods: LINC00173 expression was measured using qRT-PCR. Survival rate was analyzed through Kaplan-Meier method. CCK8, colony formation and EdU assays were performed to measure cell proliferation while transwell was used to determine cell migration and invasion. Luciferase reporter assay was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…BioMed Research International [30]. In tumor research, long noncoding RNA (lncRNA) LINC00173 could promote the development of disease by enhancing NUTF2 expression in glioma [19]. Besides, the level of NUTF2 expression was downregulated and negatively correlated with nuclear size in melanoma tissue [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BioMed Research International [30]. In tumor research, long noncoding RNA (lncRNA) LINC00173 could promote the development of disease by enhancing NUTF2 expression in glioma [19]. Besides, the level of NUTF2 expression was downregulated and negatively correlated with nuclear size in melanoma tissue [18].…”
Section: Discussionmentioning
confidence: 99%
“…An experiment in Xenopus laevis cells found that decreased level of NUTF2 may contribute to melanoma development through the regulation of cell nuclear size [18]. On the other hand, in 2020, Du et al found that NUTF2 is a downstream target of LINC00173 and regulates tumorigenesis in glioma; its overexpression awakens the proliferation, migration, and invasion of cells [19]. The association between NUTF2 and HNSCC has not been illustrated in previous studies.…”
Section: Introductionmentioning
confidence: 95%
“…Previous study had found that LINC00173 promotes the proliferation and migration of vascular endothelial cells in lung squamous cell carcinoma by acting as ceRNA to bind with miR-511-5p and regulate VEGFA expression ( Chen et al, 2020 ). LINC00173, which had the highest node degree in the hypomethylation-high expression gene-associated ceRNA network, has been investigated as part of the ceRNA networks of lung cancer ( Chen et al, 2020 ), breast cancer ( Fan et al, 2020 ), and glioma ( Du et al, 2020 ), but its molecular mechanism in autoimmune diseases of the nervous system was still unclear. As a constituent of one of the 15 ABL1-associated ceRNA triples, the lncRNA MALAT1 was shown to be downregulated in MG patients and to act as a ceRNA for miR-338-3p ( Kong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that NUTF2 plays vital roles in the phenotype of eyes and diabetic retinopathy via regulating the nuclear import of Ran proteins and the VEGF signaling pathway (9,10). With respect to cancer, upregulation of NUTF2 was found in glioma tissues and overexpression of NUTF2 promoted migration and proliferation of glioma cells, indicating its oncogenic role in glioma (11). However, the role of NUTF2 in other cancer types is largely unknown.…”
Section: Introductionmentioning
confidence: 99%